2014
DOI: 10.2337/dc13-1576
|View full text |Cite
|
Sign up to set email alerts
|

Interarm Blood Pressure Difference in People With Diabetes: Measurement and Vascular and Mortality Implications

Abstract: OBJECTIVEDifferences in blood pressure between arms are associated with vascular disease and increased mortality; this has not been reported in diabetes. We explored these associations, and assessed reference standard and pragmatic measurement techniques, in people with diabetes and in nondiabetic controls. RESEARCH DESIGN AND METHODSA prospective cohort study in Devon, England, recruited 727 people with type 1 or type 2 diabetes and 285 nondiabetic controls. Simultaneous repeated measurements of bilateral blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
3
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 38 publications
6
71
3
3
Order By: Relevance
“…2 Some previous reports have demonstrated a clear gradient in HRs and magnitude of IADs, 4,6,9,12,36 whereas others have not. 5,8 There were relatively few events included in analyses at the higher cut-off of ≥15 mmHg difference.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…2 Some previous reports have demonstrated a clear gradient in HRs and magnitude of IADs, 4,6,9,12,36 whereas others have not. 5,8 There were relatively few events included in analyses at the higher cut-off of ≥15 mmHg difference.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…23,24 Thus simultaneous, automated repeated measurements of IAD should be a reference standard for epidemiological study. 10 However, the authors have found that a single sequential pair of measurements can exclude confirmed IAD with a high negative predictive value, 11,12 and designed this study to investigate whether IADs detected by this simple method can also predict survival differences.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, we found a significant correlation between IASBPD and mean right arm SBP and peak mean hscTnT. Clark et al [21] examined 727 patients with DM and found increased IASBPD was independently associated with peripheral artery disease, diabetic retinopathy, and chronic renal disease. Follow-up of these patients demonstrated increased cardiovascular mortality in patients with IASBPD ≥ 10 mm Hg.…”
Section: Discussionmentioning
confidence: 92%
“…The prevalence of high sIAD (sIAD ≥10 mmHg) varies across ethnic groups and countries, and it tends to be higher in patients with diabetes mellitus and hypertension [16,17]. Inaddition, sIAD levels have been found to be associated with a significantly increased risk of future cardiovascular events [18].…”
Section: V Discussionmentioning
confidence: 99%